An autofluorescence-based method for the isolation of highly purified ventricular cardiomyocytes. Issue 3 (14th December 2017) - Larcher, Veronica; Kunderfranco, Paolo; Vacchiano, Marco; Carullo, Pierluigi; Erreni, Marco; Salamon, Irene; Colombo, Federico Simone; Lugli, Enrico; Mazzola, Marta; Anselmo, Achille; Condorelli, Gianluigi
Abstract: Aims: The aim of our study was to set up a simple and reliable isolation method of living ventricular cardiomyocytes (vCMs) for molecular and biological studies. Methods and results: A standard technique for the retrograde perfusion of an enzymatic solution was used to isolate cardiac cells from adult mouse heart. Fluorescence-activated cell sorting (FACS) on adult murine cardiac ventricle cells was performed, comparing the intrinsic autofluorescence in the FITC channel and the forward scatter (FSC) parameter in order to isolate highly fluorescent cells. The expression of cell-specific mRNAs was assessed with real-time PCR in cells sorted on the basis of their FITC and FSC characteristics. We identified two distinct subpopulations of cells harvested after retrograde perfusion of wild-type heart: FITC high /FSC dim and FITC dim /FSC high . Immunophenotyping and mRNA analysis (qPCR and RNA sequencing) revealed that only FITC high /FSC dim cells were highly enriched in CM markers. Genes with high expression in endothelial cells and fibroblasts were enriched in the FITC dim /FSC high subpopulation. With the use of tdTomato fl/fl -α-myosin heavy chain MerCreMer +/− mouse heart, we found that tdTomato-positive vCMs were present in the FITC high /FSC dim region but were only rare in the FITC dim /FSC high fraction. Conclusion: We have developed a simple and reliable method for the isolation of highly purified vCMs from the adult murine myocardium, avoiding fixation and permeabilization steps. These isolated vCMs can be used in particular for detailed molecular studies, avoiding contamination with other myocardial cell types.